THE RENDERING OF RAILWAY-RELATED ABBREVIATED TERMS (ACRONYMS AND ABBREVIATIONS) IN TRANSLATION FROM ENGLISH - Kurbanova Ilmira Sharifovna (Western European Studies, 2025)
Translating railway-related abbreviated terms (acronyms and abbreviations) from English into other languages is a critical aspect of technical communication in the railway industry. These terms, commonly found in operational documents, manuals, and international standards, require precise translation to ensure clarity and accuracy in the target language. This study examines the various strategies used to render these terms, including transliteration, borrowing, descriptive translation, and calque. It discusses the challenges involved in translating railway terminology into Russian and Uzbek. By considering both linguistic and cultural factors, the research highlights the role of industry-specific glossaries, the collaboration with technical experts, and the integration of modern translation tools in achieving effective translations. The study contributes to a deeper understanding of the translation process for technical terms in the railway sector and offers practical insights for ensuring consistency and clarity in multilingual railway communication
Keywords: railway terminology; translation strategies; acronyms